Support Groups Based on the Health Promotion Model Approach to Improving the Health of the Elderly with Gout - Tomasoa, Valensya; Feby Manuhutu; Junianto Tri Prasetyo (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
The elderly are a vulnerable group to the problem of gout. The 2018 Riskesdas data in Indonesia showed a 45% increase in age prevalence. The prevalence of gouty arthritis in Indonesia is high at 65-74 years (51.9%) and ≥ 75 years (54.8%). Maluku Province has a prevalence of 18.6-47.6 %. Diseased joints (pain consequence) are highest in the Aru Islands (9.63%), and Ambon is in the top position (2nd, 7.15%). Recorded data from Air Salobar Health Center, a health center in Ambon City, indicates that the number of elderly individuals with Gout in 2023 was 83 people. There are efforts made​ to improve the health of the elderly, including promotional efforts such as Support Groups, which employ an approach based on the Health Promotion Model (HPM) as a first step to promote healthy behaviors and desires among the elderly. Research objectives. This is a see-influence support group-based approach to a health promotion model for addressing problems in elderly health behavior related to gout. Design Study: This is a one-group pre-test and post-test design. The total sample in the study consisted of 83 elderly individuals suffering from Gout, selected using a purposive sampling technique. Data analysis employed the Wilcoxon test because the data were not normally distributed. Research results demonstrate a difference before and after the given support group intervention, based on the Health Promotion model, for improving elderly health behaviors. The pre-test results of the intervention are 9.33, while the post-test results are 11.27, with an average difference of 1.94 and a P-value of 0.000. Therefore, we can conclude that a support group has an influence on the approach of the Health Promotion Model towards improving behavioral health in the elderly with gout. Research on topics considered important and relevant to the problem of elderly individuals with gout recommends examining the factors and appropriate interventions to improve the quality of life for elderly people experiencing gout.